PERLAWANAN ULAMA MINANGKABAU TERHADAP KEBIJAKAN KOLONIAL DI BIDANG PENDIDIKAN AWAL ABAD XX - Erman Erman (Universitas Islam Negeri Imam Bonjol Padang, 2015)
The resistance of Minangkabau’s scholars against colonial policy of education in the early of 20th centurystarted from a scientific study has revealed that the pre-conditions that led to the birth of the movement is thepenetration of the colonial government against the people in this area and plan the implementation of policiesin the field of education, namely Ordinance 1928 and teachers’ Ordinance in 1932. This historical experiencewas seen by scholars Minangkabau might impede the freedom and the rights to broadcast the Islamic religion.Various reactions appeared and Islamic ideology seems to be the main driving to oppose colonial rule relatedteachers’ ordinancy and illegal schools. The spirit of nationalism that was born at the beginning of the 20thcentury were also encouraged scholars to take the fight against the colonial policy. In line with this goal, thescholars utilizing the network that has been built on Islamic educational institutions in the past to build aresource (strength) and then to form a committee as institutional resistance. Resistance itself they did in theform of protests by the general meeting of Minangkabau’s scholars and then proceed with the delivery of voteof no confidence to the colonial government. The resistance impacted the emerging alliance of young and oldscholars, the birth of a radical political party in Minangkabau and the pressure of the colonial government